Uncovering Clinical Principles and Techniques to Address Minority Stress, Mental Health, and Related Health Risks Among Gay and Bisexual Men. - Pachankis, John E (Clinical psychology : a publication of the Division of Clinical Psychology of the American Psychological Association, 2014)
Gay and bisexual men disproportionately experience depression, anxiety, and related health risks at least partially because of their exposure to sexual minority stress. This paper describes the adaptation of an evidence-based intervention capable of targeting the psychosocial pathways through which minority stress operates. Interviews with key stakeholders, including gay and bisexual men with depression and anxiety and expert providers, suggested intervention principles and techniques for improving minority stress coping. These principles and techniques are consistent with general cognitive behavioral therapy approaches, the empirical tenets of minority stress theory, and professional guidelines for LGB-affirmative mental health practice. If found to be efficacious, the psychosocial intervention described here would be one of the first to improve the mental health of gay and bisexual men by targeting minority stress.